Delta-Polygon Autotransformer Based 24-Pulse Rectifier for Switching Mode Power Supply - Chun-ling Hao; Xiao-qiang Chen; Hao Qiu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn medium and high power capacity switching mode power supply (SMPS), power quality at the AC side is often severely distorted. In this paper, a small magnetic rating delta-polygon autotransformer based 24-pulse rectifier feeding SMPS is designed, constructed, and simulated for harmonic mitigation. Various auto-wound transformers for the 24-pulse AC-DC converter are discussed and compared in terms of magnetic rating and power quality indices, in order that the optimal autotransformer structure can be chosen. The effect of load variation on the proposed 24-pulse rectifier is also analyzed. Moreover, performance of the 6-, 12-, and 18-pulse rectifiers based on delta-polygon autotransformer are studied through comparison. Results demonstrate that the total harmonic distortion of utility current is lower than 6.10% and unity power factor is achieved under varying load.